Empowering Communities: The Impact of Emergency First Aid Training on Knowledge and Readiness among Health Cadres - Trisyani, Yanny; Sugiharto, Firman; Emaliyawati, Etika; Nuraeni, Aan; Anna, Anastasia; Eli Kosasih, Cecep; Mirwanti, Ristina; Nurhamsyah, Donny; Prawesti, Ayu (Media Karya Kesehatan, 2025)
Many emergency situations require immediate first aid. The community plays a crucial role in saving victims of cardiac arrest or traffic accidents, which are among the leading causes of premature death in Indonesia. Unfortunately, the level of public knowledge and preparedness in providing first aid remains low, highlighting the need for improvement through education and training. Community health cadres were chosen as the target group because they are closely connected to the community, easily accessible, and can act as first responders before professional medical personnel arrive. This study aimed to enhance the knowledge and readiness of community cadres in recognizing and providing effective first aid through CPR and first aid training in Pangandaran Village. A pre-experimental one-group pre-test and post-test design was used, involving 33 participants selected through accidental sampling. Data analysis was conducted using a paired sample t-test. The results showed a significant improvement (p<0.05) in the cadres’ knowledge and preparedness after the training. Based on these findings, it is recommended that similar training programs be conducted regularly by health institutions and community organizations to strengthen the capacity of cadres in providing first aid, thereby increasing the survival rate of victims of accidents and cardiac arrest within the community.Keywords: Accident, cardiac aArrest, knowledge, preparedness.